Affective-cognitive design of product ecosystems for user experience - Zhou, Feng (2012)
As industry sectors mature, a critical challenge confronting many companies is how to provide users with engaging experiences within a product ecosystem (e.g., a subway station ecosystem). User experience goes far beyond cognitive aspects to encompass affective aspects, where the former accommodates users’ cognitive capabilities, tendencies, and limitations while the latter concerns how to elicit desirable emotional responses from users. Both aspects have major impacts on each other and importantly influence user satisfaction.